Looking beyond the intervertebral disc: the need for behavioral assays in models of discogenic pain. Issue 1 (10th August 2017) - Mosley, Grace E.; Evashwick‐Rogler, Thomas W.; Lai, Alon; Iatridis, James C.
Abstract: Orthopedic research into chronic discogenic back pain has commonly focused on aging‐ and degeneration‐related changes in intervertebral disc structure, biomechanics, and biology. However, the primary spine‐related reason for physician office visits is pain. The ambiguous nature of the human condition of discogenic low back pain motivates the use of animal models to better understand the pathophysiology. Discogenic back pain models must consider both emergent behavioral changes following pain induction and changes in the nervous system that mediate such behavior. Looking beyond the intervertebral disc, we describe the different ways to classify pain in human patients and animal models. We describe several behavioral assays that can be used in rodent models to augment disc degeneration measurements and characterize different types of pain. We review rodent models of discogenic pain that employed behavioral pain assays and highlight a need to better integrate neuroscience and orthopedic science methods to extend current understanding of the complex and multifactorial pathophysiology of discogenic back pain.